Emergence of social intelligence in social network: A quantitative analysis for agent-mediated PKM processes - Ismail S.; Ahmad M.S. (2023)
Social intelligence has been coined by authors in many aspects, with one of them being the sociability characteristics of a software agent in performing tasks over social network. This concept has been expanded from personal knowledge management (PKM) frameworks using agent mediation, where intelligent agents are assigned with tasks to assist their human counterparts. In recent studies, PKM processes are understood to be a series of getting knowledge, analysing/understanding knowledge, sharing/publishing knowledge and connecting to others for knowledge over the Internet and social network. The critical issue of this concept involves identifying and 'locating' knowledge experts for further enlightenment of one's personal knowledge. Taking into considerations the advantages of social network and the similarities between PKM processes and Nonaka's SECI model, the emergence of social intelligence are investigated in this paper by analysing the responses from a questionnaire survey on PKM processes over the social network. This paper also discusses the limitations of this research vis--vis the current situation where e-mail is still seen as the only reliable way to manage personal knowledge. It then recommends future works in the realm of social intelligence, involving software agents. 2011 IEEE.